The 25th anniversary of the journal: editor’s introduction - Zavadskas, Edmundas Kazimieras; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2019)
"The 25th anniversary of the journal: editor’s introduction", Technological and Economic Development of Economy, 25(3), 365-368.